Solving Integral Representations Problems for the Stationary Schrödinger Equation - Yudong Ren (Abstract and Applied Analysis)
When solutions of the stationary Schrödinger equation in a half-space belong to the weighted Lebesgue classes, we give integral representations of them, which imply known representation theorems of classical harmonic functions in a half-space.